Psychosocial adjustment of children with hearing impairment - Calantas, Michael Vincent S. (Universidad de Zamboanga Journal : Official Peer Reviewed Journal Publication, 2014)
This study entitled "psychosocial adjustment of children with hearing impairment", aimed to determine he following: (1) the factors influencing the psychosocial adjustment of children with hearing impairment (2) to what extent do the factors like home, school and social environment affect the social adjustment of children with hearing impairment in terms of coping with: depression, indifference, low self-esteem, mistrust, inability to get along with others, lost of interest of going to school. Convenience sampling was the means to obtain respondents composed of seventeen (17) respondents; the respondents of this study consist of 17 children that are enrolled n the year 2010-2011 in the Western Mindanao State University-SPED, identified as positive in the sensory impairment. Th collection of data utilized two (2) instruments; each of the respondents are given a paper and pencil. The findings of this study were as follows: the factors which influenced the psychosocial adjustment of children with hearing impairment are home, school and social environments. With regards to the psychosocial adjustment mentioned, these children have certain coping in line with different factors mentioned. This study implies that most of the respondents with hearing impairment have almost the same experiences. The factors such as home, social and school environment do influence their psychosocial adjustment, and most of them affect their psychosocial adjustment in terms of depression, indifference, low self-esteem, mistrust, inability to get along with others and lost of interest in going to school. The findings also implied that they have the same strategies in coping with their situations such as being with their parents and friends with the same disabilities, involving themselves in activities either in their homes or in school, excelling in their classes, and making friends with other normal children and having good interpersonal relationship with them.